Kandungan Vitamin C dan Uji Aktivitas Antioksidan Teh Herbal Kombucha Daun Bidara (Ziziphus mauritiana Lam) - Siagian , Anggi Yani; Yuniarti, Rafita; Daulay, Anny Sartika; Pulungan , Ainil Fithri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Bidara leaves (Ziziphus mauritiana Lam.) have long been used in traditional medicine due to their bioactive compounds, such as flavonoids, tannins, and vitamin C. Fermenting bidara leaves into kombucha has the potential to enhance antioxidant activity through bioconversion processes carried out by starter microbes (Acetobacter xylinum and Saccharomyces cerevisiae). However, scientific data regarding the vitamin C profile and antioxidant activity of bidara leaf kombucha remain limited. Objective: This study aims to analyze the vitamin C content and antioxidant activity of bidara leaf herbal kombucha, as well as to characterize the quality of the simplisia based on the Indonesian National Standard (SNI) 4324:2014. Methods: This descriptive study involved: (1) preparation of bidara leaf simplisia, (2) 12-day kombucha fermentation, (3) phytochemical screening, (4) determination of vitamin C content using UV-Vis spectrophotometry (λ = 266 nm), and (5) antioxidant activity assay using the DPPH method (λ = 517 nm). Results: The bidara leaf simplisia met the SNI quality standards, with a moisture content of 5.33% and a total ash content of 6.73%. Phytochemical screening identified the presence of flavonoids, saponins, tannins, glycosides, steroids/triterpenoids, and alkaloids. The vitamin C content of the kombucha was 0.009 mg/g, while the IC₅₀ value for antioxidant activity was 621.2158 µg/mL, which falls into the weak category. Conclusion: Bidara leaf kombucha contains bioactive compounds and vitamin C, with weak antioxidant activity. Fermentation increases antioxidant activity compared to non-fermented bidara tea infusion (IC₅₀ = 1129.0069 µg/mL), although it remains lower than that of pure vitamin C (IC₅₀ = 3.0710 µg/mL).